2021
DOI: 10.1021/acs.nanolett.0c04834
|View full text |Cite
|
Sign up to set email alerts
|

Stimulating Extracellular Vesicles Production from Engineered Tissues by Mechanical Forces

Abstract: Extracellular vesicles (EVs) have emerged as a promising strategy to promote tissue regeneration. However, overcoming the low EV production yield remains a big challenge in translating EV-based therapies to the clinical practice. Current EV production relies heavily on 2D cell culture, which is not only less physiologically relevant to cells but also requires substantial medium and space. In this study, we engineered tissues seeded with stem cells from dental pulp or adipose tissues, or skeletal muscle cells, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(82 citation statements)
references
References 29 publications
3
68
1
Order By: Relevance
“…Under mechanical force stimulations, the EV secretions were greatly enhanced in a process mediated by Yes-associated protein (YAP) mechanosen-sitivity. Additionally, EVs derived from mechanically stimulated tissues containing DPSCs were more potent in inducing axonal sprouting of cultured neurons than those without mechanical stimulations, suggesting the potential of those mechanically inspired EVs for the treatment of nerve injuries, including SCI and stroke [141]. Another challenge that hampers the clinical translation of EV is the lack of a standardized isolation and purification method.…”
Section: Challenges and Future Perspectivesmentioning
confidence: 99%
“…Under mechanical force stimulations, the EV secretions were greatly enhanced in a process mediated by Yes-associated protein (YAP) mechanosen-sitivity. Additionally, EVs derived from mechanically stimulated tissues containing DPSCs were more potent in inducing axonal sprouting of cultured neurons than those without mechanical stimulations, suggesting the potential of those mechanically inspired EVs for the treatment of nerve injuries, including SCI and stroke [141]. Another challenge that hampers the clinical translation of EV is the lack of a standardized isolation and purification method.…”
Section: Challenges and Future Perspectivesmentioning
confidence: 99%
“…Fortunately, MSCs are one of the most active producers of EVs [148]. EV production can be enhanced by various stimuli, such as hypoxia [149], low pH [150], 3D cell culture [151], acoustic-, electrical-, and mechanicalstimulation [152][153][154][155]. Methods for enhancing intrinsic MSC production of EVs have been reviewed elsewhere [156].…”
Section: Extracellular Vesicles: Sourcementioning
confidence: 99%
“…Haraszti et al, 2019). In addition, mechanical forces such as flow and stretching factors have also been shown to impact the secretion of stem cells via bioreactors, which elevated the production of EVs by up to 37-fold (Guo et al, 2021;Yan et al, 2021). Furthermore, Ambattu et al demonstrated that stimulating cells with high-frequency ultrasound could result in an 8-10-fold increase in the yield of exosomes (Ambattu et al, 2020).…”
Section: Chemical/physical Stimulationmentioning
confidence: 99%
“…Meanwhile, study of the culture condition has also identified other pathways such as Rab GTPase (Ruan et al, 2018;Z. Wu et al, 2021) and YAP (Guo et al, 2021) associated with exosome releasing. Such findings could be leveraged in combination to produce stem cells with an exosome-productive genotype, in this way the application of exosomes may be extensively expanded.…”
Section: Genetic Engineeringmentioning
confidence: 99%